Traditional Game on The Social Skill of Students in The Social Science Learning of Elementary School - Nugraha, Yoga Awalludin; Handoyo, Eko; Sulistyorini, Sri (Journal of Primary Education, 2018)
The purpose of this research was; to determine the effect of traditional game based learning on the social skill students; and to find the different effect of traditional game based learning and expository learning on social skills students. This type of research is quantitative method with pre-test post-test control group design. Samples of this research were the fourth grade students of SDN Cieurih with 30 students as experimental group and SDN Cipicung with 25 students as control group. Data collection techniques used non-test techniques, including interview guides, observation guidelines, and documentation. The results showed that; there is a significant influence on learning that using traditional game to social skill of students, this is based on independet ttest result 0.00 < 0.05, and N-Gain 0.40 which is in medium category; and there is a very high average, high, sufficient, and low average difference in the social skills of students on traditional game-based learning with expository learning. This is evidenced by the acquisition of one way ANOVA test results of 0.00 < 0.05. Furthermore, post hoc test to determine the most significant group, obtained the largest mean difference in very high group, that is 31.333. The social aspect of tradisional game in social science learning were discussed.